Kritik Sosial dalam Cerpen Ratun Jogéd Karya Pandé Putu Alit Antara - Lisna Asih, Ni Nyoman; Dewarman, I Wayan; Pratama, I Putu Ogik; Wika, I Kadek; Paramitha, Ni Made Ayu Susanthi Pradnya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Social criticism is someone's thoughts about existing problems that are not in accordance with existing norms and goals in society. This research aims to determine the social criticism contained in the short story Ratun Jogéd by Pandé Putu Alit Antara. The analytical method used in this research is descriptive qualitative and recording techniques. The results and discussion of the research show that the social criticism contained in short stories is social criticism of parents' wrong parenting patterns, social criticism of abuse of love and social criticism of moral deviation. The appearance of the short story by Pandé Putu Alit Antara proves the existence of social inequality in Balinese society.